Influence of Palm Oil Fuel Ash on Mechanical Properties of Ultra-High-Performance Concrete - Abdul Kudus, Sakhiah; Mustaffa, Nur Kamaliah; Shahidan , Shahiron (International Journal of Sustainable Construction Engineering and Technology, 2022)
Palm oil fuel ash (POFA) is a by-product of the burning of waste material at the palm oil power plant. The disposal of POFA becomes an issue since Malaysia was among the largest palm oil producer. One thing led to another, improper waste management of POFA may cause air and water pollution. Therefore, the implementation of POFA in construction can help to reduce the problem of solid waste disposal as it was considered as a supplementary cementitious material. This research study was an effort to determine the mechanical properties of ultra-high-performance concrete (UHPC) with POFA addition. The development of building materials with improved characteristics and their application for increasing structure durability and sustainability is one of the goals in construction sector. In this study, the percentage of POFA used as a cement replacement was 5%, 10% and 15% by binder weight. Several tests have been conducted to determine the results for several specific parameters. The results were collected from slump test and compressive strength test. Tabulation and graph illustration were the methods used to present the data. The workability test conducted showed that with the increase of POFA addition to the UHPC, the workability of fresh concrete was reduced. Meanwhile, the compressive strength at 28 days, UHPC with 5% of POFA addition showed the maximum value of compressive strength at 84.12 N/mm2.